Assessment of oral health-related quality of life, measured by OHIP-14 and GOHAI, and psychological profile in burning mouth syndrome: a case-control clinical study. - Aragão, Meiz (2021)
Objectives: To evaluate the oral health-related quality of life (OHRQoL) of patients with burning mouth syndrome (BAS), comparing the Oral Health Impact Profile-14 (OHIP-14) and Geriatric Oral Health Assessment Index (GOHAI) tests, evaluating its dependence on pain, anxiety and depression and, secondly, to analyze changes in time after treatment with psychotropic drugs.Methods: Twenty-six patients and 26 controls were included. The GOHAI, OHIP-14, visual analogue scale (VAS) and Hamilton rating scales for depression and anxiety (HAM-D and HAM-A) were performed at baseline (time 0) and after 6 months of treatment (time 1 ). Descriptive statistics, the nonparametric Mann-Whitney test for two independent samples and the nonparametric Wilcoxon test for two paired samples were used.Results: The scores of all outcome measures were statistically significantly different between cases and controls ( P < 0.001), with a strong correlation between GOHAI and OHIP-14 ( P < 0.001). Patients with BMS showed a statistically significant improvement in VAS, HAM-D and HAM-A scores from time 0 to time 1 (P<0.001), and in OHIP-14 scores (P<0.004**) after treatment, but no statistically significant difference in GOHAI score (0.464).Conclusions: Patients with burning mouth syndrome had lower scores on all scales compared to healthy individuals with a low OHRQoL. The OHIP-14 assigns greater weight to psychological and behavioral outcomes in the assessment of oral health than the GOHAI and, therefore, is a more effective questionnaire in terms of assessing treatment response. BMS management can improve pain, anxiety and depression and OHRQoL.